Comparative pharmacoeconomic analysis of rituximab and traditional tacrolimus regimens in membranous nephropathy in China - Zeng, Li; Chen, Huihui; Xiang, Heng; Zeng, Mengru; Zhou, Mi; Tan, Chongqing; Liu, Hong; Chen, Guochun (Frontiers in Pharmacology, 2024)
Background: Rituximab (RTX) is a monoclonal antibody that selectively targets CD20 and is frequently used in the treatment of membranous nephropathy (MN). Analysis of the therapeutic efficacy and safety of RTX in treating MN in practice and a comparative pharmacoeconomic analysis of the RTX and traditional tacrolimus (TAC) regimens can provide valuable insights to aid decision-making by the government and relevant medical insurance departments. Methods: We conducted a statistical analysis of medical records from patients diagnosed with MN who underwent RTX treatment between January 1, 2019 and January 1, 2023. The TAC data were obtained from the clinical literatures. The efficacy rates and incidence of adverse effects (AEs) were calculated to compare the efficacy and safety of RTX and TAC. Based on the patient’s disease status, we developed a Markov model to compare the total cost, remission rate, and incremental cost-effectiveness ratio (ICER) of the two regimens. Both univariate and probability sensitivity analyses were performed to validate the stability of the developed model. Results: The RTX group enrolled 53 patients with MN, and the 12-month overall efficacy rate was not significantly different from that of the TAC group with 35 patients (86.79% vs. 71.4%, p = 0.0131); however, the relapse rate was significantly lower in the RTX group (3.77% vs. 22.8%, p = 0.016). The RTX group demonstrated no severe AEs (SAEs), while the TAC group demonstrated six cases of SAEs, including 4 cases of severe pneumonia, 1 case of lung abscess and 1 case of interstitial lung disease, accounting for 7.89% of traditional tacrolimus-treated patients. The baseline analysis results revealed that over a 5-year post-treatment period, RTX increased quality-adjusted life years (QALYs) by 0.058 and costs by ¥7,341. Assuming three times the 2022 domestic gross domestic product as the willingness-to-pay (WTP) threshold per QALY, the ICER of RTX compared to TAC was ¥124,631.14/QALY, which is less than the WTP threshold of ¥257,094/QALY, indicating that RTX treatment is approximately two times more cost-effective compared to TAC. Conclusion: The current analysis indicates that despite the expensive unit price of RTX, it remains a cost-effective treatment option for MN compared to TAC.